Arrecadação governamental e sistema tributário como resultados políticos - Souza, Gustavo Moreira de (2014)
This paper introduces simultaneous choices of the political, taxation and expenditure government systems in a dynamics macroeconomic model of political economy with incomplete markets where the size of government must be decided in each period. The paper also evaluates the effect of each one of these institutions on the political equilibrium. The inclusion of these variables makes the model more realistic and makes possible the study of how government policy is chosen by society. The more general specification of the model calibrated to the EUA reproduced the effective tax rate and capital-labor tax rate observed in data.